PENGARUH INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI KOTA PAREPARE - Mega Wahyuni; Muhammad Nur; Fajar Ladung (Cateris Paribus Journal, 2026)
This study aims to analyze the effect of the Human Development Index (HDI) on economic growth in Parepare City during the 2014–2023 period. The method used is a quantitative approach with simple linear regression analysis using secondary data sourced from the Central Statistics Agency (BPS) of Parepare City. The independent variable in this study is the Human Development Index, while the dependent variable is economic growth measured by the Gross Regional Domestic Product (GRDP) growth rate at constant prices. Data processing was performed using SPSS version 29. The results indicate that the HDI has a negative but insignificant effect on economic growth in Parepare City, as evidenced by a regression coefficient of -0.963 with a significance level of 0.156 > 0.05. The R² value of 0.235 indicates that the HDI accounts for only 23.5% of the variation in economic growth, while 76.5% is influenced by other factors outside the model. These findings suggest that the annual increase in the HDI in Parepare City has not been accompanied by an improvement in the quality of economically productive human resources, and thus has not been able to significantly drive economic growth. This situation was exacerbated by the impact of the COVID-19 pandemic in 2020, which caused an economic contraction of -0.08%. Policies are needed that are more focused on increasing productivity and the absorption of educated labor in strategic sectors.